The Columbia history of Eastern Europe in the twentieth century - Held, Joseph Hrsg (Columbia Univ. Press, 1992)
Eastern Europe in the twentieth century : "old wine in new bottles" / Stephen Fischer-Galati -- Albania / Nicholas C. Pano -- Bulgaria / Marin Pundeff -- Czechoslovakia / Sharon L. Wolchik -- Hungary on a fixed course : an outline of Hungarian history / P(c)♭ter Han(c)Łk and Joseph Held. 1918-45 / P(c)♭ter Han(c)Łk. 1945 to the present / Joseph Held -- Poland : 1918-1990 / Andrzej Korbonski -- The multiple legacies of history : Romania in the year 1990 / Trond Gilberg -- The Yugoslav phenomenon / Dimitrije Djordjevic -- Germany and Eastern Europe / Melvin Croan -- By way of a conclusion : controlled and uncontrolled change in Eastern Europe / Iv(c)Łn V(c)œlgyes